Functional potential of a new plant-based fermented beverage: Benefits through non-conventional probiotic yeasts and antioxidant properties - Alice Agarbati; Laura Canonico; Maurizio Ciani; Camilla Morresi; Elisabetta Damiani; Tiziana Bacchetti; Francesca Comitini (International Journal of Food Microbiology, 2024)

Agro-ecosystem of honeybees as source for native probiotic yeasts - Alice Agarbati; Laura Moretti; Laura Canonico; Maurizio Ciani; Francesca Comitini (World Journal of Microbiology and Biotechnology, 2024)
Probiotic microorganisms are used to improve the health and wellness of people and the research on this topic is of current relevance and interest. Fifty-five yeasts, coming from honeybee’s ecosystem and belonging to Candida , Debaryomyces , Hanseniaspora , Lachancea , Metschnikowia , Meyerozyma , Starmerella and Zygosacchromyces genera and related different species, were evaluated for the probiotic traits. The resistance to gastrointestinal conditions, auto-aggregation, cell surface hydrophobicity or biofilm formation abilities as well as antimicrobial activity against common human pathogenic bacteria were evaluated. The safety analysis of strains was also carried out to exclude any possible negative effect on the consumer’s health. The influence of proteinase treatment of living yeasts and their adhesion to Caco-2 cells were also evaluated. The greatest selection occurred in the first step of survival at the acidic pH and in the presence of bile salts, where more than 50% of the strains were unable to survive. Equally discriminating was the protease test which allowed the survival of only 27 strains belonging to the species Hanseniaspora guilliermondii , Hanseniaspora uvarum , Metschnikowia pulcherrima , Metschnikowia ziziphicola , Meyerozyma caribbica , Meyerozyma guilliermondii , Pichia kluyveri , Pichia kudriavzevii and Pichia terricola . An integrated analysis of the results obtained allowed the detection of seven yeast strains with probiotic aptitudes, all belonging to the Meyerozyma genus, of which three belonging to M. guillermondii and four belonging to M . caribbica species.

Cell-recycle batch process of Scheffersomyces stipitis and Saccharomyces cerevisiae co-culture for second generation bioethanol production - Selim Ashoor; Francesca Comitini; Maurizio Ciani (Biotechnology Letters, 2015)

Influence of Temperature and Oxygen Concentration on the Fermentation Behaviour of Candida Stellata in Mixed Fermentation with Saccharomyces Cerevisiae - Maurizio Ciani; Francesca Comitini (World Journal of Microbiology and Biotechnology, 2006)